Correlation Between ROTEM FIBTEM Maximum Clot Firmness and Fibrinogen Levels in Pediatric Cardiac Surgery Patients. (7th March 2019) - Tirotta, Christopher F.; Lagueruela, Richard G.; Madril, Danielle; Salyakina, Daria; Wang, Weize; Taylor, Thomas; Ojito, Jorge; Kubes, Kathleen; Lim, Hyunsoo; Hannan, Robert; Burke, Redmond
This study evaluated whether rotational thromboelastometry (ROTEM; Tem International GmbH, Munich, Germany) FIBTEM maximum clot firmness (MCF) can be used to predict plasma fibrinogen level in pediatric patients undergoing cardiac surgery. Linear regression was conducted to predict plasma fibrinogen level using FIBTEM MCF (0.05 level of significance). Scatter plot with the regression line for the model fit was created. Fifty charts were retrospectively reviewed, and 87 independent measurements of FIBTEM MCF paired with plasma fibrinogen levels were identified for analysis. Linear regression analysis suggested a significant positive linear relationship ( P < .0001) between plasma fibrinogen levels and MCF. Both MCF intercept and slope were significantly correlated with fibrinogen level ( P < .0001). The estimated regression equation (predicted fibrinogen = 78.6 + 12.4 × MCF) indicates that a 1-mm increase in MCF raises plasma fibrinogen level by an average of 12.4 mg/dL. The statistically significant positive linear relationship observed between MCF and fibrinogen levels ( P < .001) suggests that MCF can be used as a surrogate for fibrinogen level. This relationship is of clinical relevance in the calculation of patient-specific dosing of fibrinogen supplementation in this setting.